Testing and performance analysis of a hollow fiber-based core for evaporative cooling and liquid desiccant dehumidification - Jradi, M.; Riffat, Saffa (Taylor & Francis, 2016)
In this study, an innovative heat and mass transfer core is proposed to provide thermal comfort and humidity control using a hollow fiber contactor with multiple bundles of micro-porous hollow fibers. The hollow fiber-based core utilizes 12 bundles aligned vertically, each with 1,000 packed polypropylene hollow fibers. The proposed core was developed and tested under various operating and ambient conditions as a cooling core for a compact evaporative cooling unit and a dehumidification core for a liquid desiccant dehumidification unit. As a cooling core, the fiber-based evaporative cooler provides a maximum cooling capacity of 502 W with a wet bulb effectiveness of 85%. As a dehumidification core and employing potassium formate as a liquid desiccant, the dehumidifier is capable of reducing the air relative humidity by 17% with an overall dehumidification capacity of 733 W and humidity effectiveness of 47%. Being cheap and simple to design with their attractive heat and mass transfer characteristics and the corresponding large surface area-to-volume ratio, hollow fiber membrane contactors provide a promising alternative for cooling and dehumidification applications.